PENGARUH PENGGUNAAN REBUSAN AIR DAUN SIRIH TERHADAP LAMA PENYEMBUHAN LUKA PERINEUM PADA IBU POSTPARTUM DI RS. SARININGSIH TAHUN 2017 - Dida Wanti; Tantri Wenny Sitanggang (STIKes IMC Bintaro, 2018)
IndonesiaOne of factors which become a big contributor to the maternal mortality rate is infection. Infection in during childbirth is morbidity and mortality to postpartum mother. The biggest infection contribution of postpartum caused perineum wound that don’t well groomed. The use of antiseptic solution is recommended to help healing of perineum wound, and one of material which has antiseptic content is betel leaf.To know the influence of boiled water betel leaf to the perineum wound healing to the postpartum mother in Sariningsih hospital. This research used quasi-experiment with post-test only control group design. The number of sample here is 30 postpartum mothers, which 15 samples as treatment class and 15 samples more as control class. Technique of taking sample is consecutive sampling. Instrument that is used is observation checklist. It is to observe long healing of perineum wound. The data analysis use Mann Whiteney U test. Healing of perineum wound for 5 days more to 15 people in treatment class, 4 people in control class, than to the healing of perineum wound for less than 5 days happened in control class as much as 13 people. Score p value 0.000.There are influences of boiled water betel leaf to the long healing of perineum wound to postpartum mother. This research can be consideration in giving information about the use of boiled water betel leaf to the patient at home.